A kind of formaldehyde-free impregnating glue and preparation method thereof

By using aqueous polyurethane dispersion and polyether modified trisiloxane in the aldehyde-free impregnated glue, the problem of difficult to balance the permeability, bonding strength and scratch resistance is solved, and high surface bonding strength and wear resistance are achieved and environmentally friendly, legacy-free impregnated glue improves production efficiency and storage stability.

CN116042159BActive Publication Date: 2025-01-10WANHUA CHEM GRP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202111264511.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-28
Publication Date
2025-01-10
Estimated Expiration
2041-10-28

AI Technical Summary

Technical Problem

The existing legacy-free impregnated glue is difficult to balance the permeability, bonding strength and surface scratch resistance, and there are problems of insufficient storage stability and surface bonding strength.

Method used

The aqueous polyurethane dispersion is used, including bis(4-aminophenoxy)dimethylsilane chain extender and polyether modified trisiloxane as the penetration agent, to improve the high temperature resistance of the impregnated glue, the surface scratch resistance and Wear resistance and through specific process steps and component ratios, a semi-free impregnated glue is prepared with easy permeability, high adhesive strength and good surface performance.

Benefits of technology

It significantly improves the surface bonding strength, scratch resistance and wear resistance of impregnated glue, extends storage time, improves production efficiency, and reduces harm to the human body, making it more environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003325461100000021
    Figure BDA0003325461100000021
  • Figure BDA0003325461100000022
    Figure BDA0003325461100000022
  • Figure BDA0003325461100000061
    Figure BDA0003325461100000061
Patent Text Reader

Abstract

The invention discloses a formaldehyde-free impregnating glue, the raw materials of which include the following components: aqueous polyurethane dispersion, defoamer, spreader, thickener, wear-resistant agent, and water. The preparation method is: adding the aqueous polyurethane dispersion into a dispersion kettle, then sequentially adding the defoamer, spreader, wear-resistant agent, and water under stirring conditions, and finally adding the thickener to adjust to a suitable viscosity to obtain the formaldehyde-free impregnating glue. The impregnating glue of the invention has the characteristics of being formaldehyde-free, easy to penetrate, high bonding strength, good surface performance, and long storage time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of adhesives, and in particular relates to formaldehyde-free impregnating adhesive and a preparation method thereof. Background Art

[0002] With the rapid development and maturity of the decoration industry, people's requirements for indoor environment are gradually increasing. How to reduce free formaldehyde in decorative panels has become a hot topic in the industry. At present, Wanhua Chemical has a mature formaldehyde-free solution for the manufacture of artificial panels (CN201710447741.8), so the development of formaldehyde-free impregnation glue for decorative paper has become the key to solving the problem.

[0003] China's public patent CN 110450239 A introduces a method for preparing a new type of formaldehyde-free impregnated film paper, which has good performance in surface bonding strength, resistance to cold and hot cycles, cracking and texture, but its viscosity is large, particle size is large, and storage stability is poor. CN111411543 A introduces an adhesive for formaldehyde-free impregnated film paper and its preparation method. Its polyurethane emulsion has a small particle size, a small molecular weight, and a moderate viscosity, so that the impregnated adhesive can penetrate into the paper better, solving the problem of paper damage after ordinary resin adhesive impregnation, and at the same time increasing the amount of glue attached to the impregnated film paper. However, the solid content is low and the molecular weight is small, and there is a problem of low surface bonding strength. CN 111496948 A introduces a formaldehyde-free artificial board with impregnated film paper and its preparation method, which is prone to hot sticking problems when using acrylic emulsion.

[0004] Currently, urea-formaldehyde glue or melamine-formaldehyde glue is widely used in the impregnation glue industry. Relevant researchers are developing formaldehyde-free solutions, but they cannot achieve a balance in performance such as permeability, bonding strength and surface scratch resistance. These requirements have posed considerable challenges to relevant researchers. Summary of the invention

[0005] The primary purpose of the present invention is to provide an aldehyde-free impregnating glue, which adopts a special aqueous polyurethane dispersion to improve high temperature resistance, surface scratch resistance and wear resistance. At the same time, the aldehyde-free impregnating glue provided is of biological origin, formaldehyde-free, easy to penetrate, high bonding strength, good surface performance and long storage time.

[0006] To achieve the above-mentioned object of the invention, the technical solution of the present invention is as follows:

[0007] A formaldehyde-free impregnating adhesive, the impregnating adhesive comprising the following components in parts by weight:

[0008]

[0009] Wherein, the aqueous polyurethane dispersion contains a bis(4-aminophenoxy)dimethylsilane chain extender with the following structure:

[0010]

[0011] The present invention reduces the surface tension of the impregnating glue by introducing a small molecule chain extender with silicon elements into the main chain, and uses a polyether-modified trisiloxane with a special structure as a spreading agent to make the obtained impregnating glue easy to penetrate the substrate, thereby improving the surface bonding strength; at the same time, the rigid benzene ring structure in the chain extender can improve the scratch resistance and wear resistance of the impregnating glue.

[0012] In the present invention, the aqueous polyurethane dispersion is an aqueous aliphatic polyurethane dispersion with a particle size of 50-150 nm and a solid content of 35-40%.

[0013] In the present invention, the waterborne polyurethane dispersion is prepared by reacting aliphatic diisocyanate, polyol, catalyst, chain extender and active monomer, emulsifying with water and removing the solvent.

[0014] In the present invention, the aliphatic diisocyanate is selected from one or more of pentamethylene diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, and dicyclohexylmethane diisocyanate, preferably hexamethylene diisocyanate and / or dicyclohexylmethane diisocyanate.

[0015] In the present invention, the polyol is a mixture of at least one crystalline polyol with a number average molecular weight of 200-5000 and at least one non-crystalline polyol with a number average molecular weight of 200-5000; preferably, it is a mixture of a crystalline diol with a number average molecular weight of 1000-3000 and a non-crystalline diol with a number average molecular weight of 2000-3000; more preferably, the non-crystalline diol is a polypropylene carbonate polyol prepared by copolymerization using carbon dioxide and propylene oxide as raw materials, and the crystalline diol is a polyester diol prepared by reacting 1,4-butanediol and / or 1,6-hexanediol with adipic acid.

[0016] In the present invention, the active monomer is one or more of N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, and 1,3-bis(aminopropyl)tetramethyldisiloxane, preferably one or more of N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltriethoxysilane, and N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane.

[0017] In the present invention, the defoamer is an organosilicon defoamer, preferably BYK-024 and / or BYK-028.

[0018] In the present invention, the thickener is one or more of fumed silica, sodium carboxymethyl cellulose, hydroxypropyl methyl cellulose, carbomer, and lithium magnesium silicate, preferably hydroxypropyl methyl cellulose and / or lithium magnesium silicate.

[0019] In the present invention, the spreading agent is a polyether-modified trisiloxane wetting agent, preferably one or more of Silwet 618, Silwet 408, and RH-288.

[0020] In the present invention, the wear-resistant agent is one or more of silicon dioxide suspension, aluminum oxide suspension, and silicone resin emulsion, preferably 50%-60% silicone resin emulsion and / or 10% aluminum oxide suspension.

[0021] Another object of the present invention is to provide a method for preparing the formaldehyde-free impregnating glue.

[0022] A method for preparing the formaldehyde-free impregnating glue, the method comprising the following steps:

[0023] S1: Dispersing thickener and water to form pre-gel;

[0024] S2: adding the aqueous polyurethane dispersion into a dispersion kettle and stirring (I), adding a defoamer and a spreading agent and stirring (II), adding an anti-wear agent and stirring (III), adding a pre-gel and an auxiliary agent and stirring (IV), adjusting the viscosity, and preparing a formaldehyde-free impregnating glue.

[0025] In the present invention, the dispersing process in S1 is 2000-3000 rpm and the time is 15-25 min.

[0026] In the present invention, the proportion of the thickener in the pre-gel described in S1 is 15-30wt%.

[0027] In the present invention, the stirring (I) in S2 has a rotation speed of 300-500 rpm; the stirring (II) is stirring for 10 min at a rotation speed of 300-500 rpm; the stirring (III) is stirring for 10 min at a rotation speed of 300-500 rpm; the stirring (IV) is stirring for 15 min at a rotation speed of 500-800 rpm.

[0028] In the present invention, the viscosity of S2 is adjusted to 100-800 mPa·s.

[0029] Compared with the prior art, the positive effects of the present invention are:

[0030] (1) It does not contain formaldehyde, changes the traditional impregnation glue system, reduces harm to the human body, and is more environmentally friendly

[0031] (2) Easy to penetrate, improving the permeability to the inside of the substrate, increasing the surface bonding strength while improving production efficiency; the wear resistance is increased by 20-30% compared to the traditional system, and the scratch resistance is significantly improved compared to the existing formaldehyde-free system. DETAILED DESCRIPTION

[0032] The embodiments of the present invention are further described below in conjunction with examples, but the present invention is not limited to the listed examples, and should also include any other known changes within the scope of the rights claimed by the present invention.

[0033] Source of raw materials

[0034] Polypropylene carbonate polyol: PPCD221, hydroxyl value 56 mgKOH / g, number average molecular weight 2000, Guangdong Dazhi Environmental Protection Technology Co., Ltd.;

[0035] Polybutylene adipate: PBA2000, hydroxyl value 56 mgKOH / g, number average molecular weight 2000, Yantai Huada Chemical);

[0036] Bis(4-aminophenoxy)dimethylsilane: purity 95%, Merrill;

[0037] Dicyclohexylmethane diisocyanate: NCO content ≥ 31.8%, Wanhua Chemical;

[0038] MPEG: polyethylene glycol monomethyl ether, hydroxyl value 46.75 mgKOH / g, number average molecular weight 1200, functionality 1, Lotte, South Korea;

[0039] A-95: N-(2-aminoethyl)-2-aminoethanesulfonic acid, solid content 51±2% aqueous solution, amine value 260±20mgKOH / g, EVONIK, Germany;

[0040] IPDA: isophoronediamine, Wanhua Chemical Group Co., Ltd.;

[0041] Wear-resistant agent MPF52E: solid content about 55%, Wacker Chemical;

[0042] Wear-resistant agent aluminum oxide: ZC-L10 Zhongchao shares;

[0043] Thickener lithium magnesium silicate WS3: density 2300-2600kg / m 3 , Leivos, Germany;

[0044] Spreading agent Silwet 618: purity ≥90%, Momentive High-Tech Materials;

[0045] Spreading agent Silwet 408: purity ≥90%, Momentive High-tech Materials;

[0046] Spreading agent RH288: purity ≥90%, Zhejiang Runhe;

[0047] Thickener fumed silica: AEROSIL 200, purity ≥99%, Evonik, Germany.

[0048] Characterization method: (refer to GB / T 28995-2012, GB / T 17657-2013, GB / T 15102-2017)

[0049] 1) Penetration time: immerse the base paper into the impregnating glue and record the time when the base paper is completely soaked;

[0050] 2) Glue amount: X = (m2-m1) / m1*100, where: X is the glue amount, m1 is the mass of the base paper, and m2 is the weight of the impregnated paper after drying;

[0051] 3) Surface bonding strength: according to the method specified in 4.16 of GB / T 17657-2013;

[0052] 4) Cracking resistance: According to the method specified in 4.36 of GB / T 17657-2013;

[0053] 5) Scratch resistance: According to the method specified in 4.39 of GB / T 17657-2013, the load is 1.50N;

[0054] 6) Wear resistance: according to the method specified in 4.44 of GB / T 17657-2013;

[0055] 7) Folding fracture angle: The maximum angle at which the impregnated film paper does not break when it is bent is recorded as the folding fracture angle;

[0056] 8) Formaldehyde emission: according to the method specified in 4.59 of GB / T 17657-2013;

[0057] 9) Storage time: The longest time during which the impregnated gel is stored at 35°C without gelation or precipitation is recorded as the storage time.

[0058] Device information:

[0059] 1) Multifunctional disperser: EDS1000, Shanghai Pushen Chemical Machinery Co., Ltd.;

[0060] 2) Universal testing machine: AI-7000M, high-speed rail testing;

[0061] 3) Scratch tester: HY-IV, Shanghai Modern Environmental Engineering Technology Co., Ltd.;

[0062] 4) Blast drying oven: GT-7024-EL, high-speed rail testing;

[0063] 5) Constant temperature and humidity chamber: GPL-2, Espec Experimental Instruments (Guangdong) Co., Ltd.;

[0064] 6) TABER Abrasion Tester: HY-768, Taiwan Hengyu Instrument Co., Ltd.

[0065] Example 1

[0066] The formaldehyde-free impregnating adhesive is prepared from the following raw materials in parts by weight:

[0067]

[0068]

[0069] In this example, waterborne polyurethane dispersion I was prepared as follows:

[0070] 190g of dehydrated polypropylene carbonate polyol PPCD221 composed of carbon dioxide and propylene oxide, 60g of dehydrated polybutylene adipate PBA2000, 61g of hexamethylene diisocyanate, 9g of dicyclohexylmethane diisocyanate, 100g of acetone, and 7.5g of MPEG were added to a 1L four-necked round-bottom flask equipped with a nitrogen inlet and outlet, and the mixture was stirred at 85°C for 3h to react until the NCO% reached 6.97%, 4.2g of neopentyl glycol was added to react for 1 hour and the temperature was lowered, 200g of acetone was added, and 5.2g of A-95 (N-(2-aminoethyl)-2-aminoethanesulfonic acid, 9.3g of IPDA, 21.2g of bis(4-aminophenoxy)dimethylsilane, 3.9g of a 50% concentration of diethanolamine aqueous solution, and 3.2g of dissolved N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane was mixed with 20g acetone, reacted for 10 minutes under stirring, and 600g deionized water was added under rapid stirring to disperse. Acetone was separated by distillation to obtain a polyurethane dispersion. Its particle size was 57nm and the solid content was 35wt%.

[0071] In this example, the aldehyde-free impregnating glue is prepared as follows:

[0072] S1: Add WS3 and deionized water into a high-speed disperser in sequence, at 3000 rpm, and disperse for 25 min to prepare a 20% pre-gel for later use;

[0073] S2: Add the aqueous polyurethane dispersion into the dispersion kettle, and stir the shaft at a speed of 400 rpm; add the defoamer and the spreading agent, stir for 10 min, and stir the shaft at a speed of 400 rpm; add the anti-wear agent, stir for 10 min, and stir the shaft at a speed of 500 rpm; finally, add anhydrous ethanol, deionized water, and pre-gel, stir for 15 min, and stir the shaft at a speed of 750 rpm, and adjust the viscosity to 740 mPa·s to prepare the formaldehyde-free impregnating glue.

[0074] Example 2

[0075] The formaldehyde-free impregnating adhesive is prepared from the following raw materials in parts by weight:

[0076]

[0077] Preparation of waterborne polyurethane dispersion II in this example:

[0078] 100 g of dehydrated polypropylene carbonate polyol PPCD221 composed of carbon dioxide and propylene oxide, 150 g of dehydrated polybutylene adipate PBA2000, 14 g of isophorone diisocyanate, 53 g of dicyclohexylmethane diisocyanate, 95 g of acetone and 7.5 g of MPEG were added into a 1L four-necked round-bottom flask equipped with a nitrogen inlet and outlet, and the mixture was stirred at 85°C for 3 h until the NCO% reached 3.92%. The temperature was lowered and 210 g of acetone was added. Under stirring, 3.3 g of A-95 (N-(2-aminoethyl)-2-aminoethanesulfonic acid), 6.9 g of IPDA, 9.0 g of bis(4-aminophenoxy)dimethylsilane, 2 g of 50% diethanolamine aqueous solution, and 20 g of acetone in which 1.1 g of N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane was dissolved were added. The mixture was reacted for 10 min under stirring. Under rapid stirring, 550 g of deionized water was added for dispersion. Acetone was separated by distillation to obtain a polyurethane dispersion. The particle size was 78 nm and the solid content was 35 wt%.

[0079] In this example, the aldehyde-free impregnating glue is prepared

[0080] S1: Sodium carboxymethyl cellulose and deionized water are added to a high-speed disperser in sequence, at 2500 rpm, and dispersed for 25 minutes to prepare a 15% pre-gel for use.

[0081] S2: Add the aqueous polyurethane dispersion into the dispersion kettle, and stir the shaft at a speed of 300 rpm; add the defoamer and the spreading agent, stir for 10 min, and stir the shaft at a speed of 400 rpm; add the anti-wear agent, stir for 10 min, and stir the shaft at a speed of 500 rpm; finally, add anhydrous ethanol, deionized water, and pre-gel, stir for 15 min, and stir the shaft at a speed of 800 rpm, and adjust the viscosity to 535 mPa·s to prepare the formaldehyde-free impregnating glue.

[0082] Example 3

[0083] The formaldehyde-free impregnating adhesive is prepared from the following raw materials in parts by weight:

[0084]

[0085] Preparation of waterborne polyurethane dispersion III in this example:

[0086] 130 g of dehydrated polypropylene carbonate polyol PPCD221 composed of carbon dioxide and propylene oxide, 120 g of dehydrated polybutylene adipate PBA2000, 50 g of hexamethylene diisocyanate, 10 g of dicyclohexylmethane diisocyanate, 95 g of acetone and 7.5 g of MPEG were added into a 1L four-necked round-bottom flask equipped with a nitrogen inlet and outlet, and the mixture was stirred at 80°C for 3 h until the NCO% reached 5.45%. The temperature was lowered, 230 g of acetone was added, and 2.7 g of A-95 (N-(2-aminoethyl)-2-aminoethanesulfonic acid, 9.3 g of N-(2-hydroxyethyl)-ethylenediamine, 4.2 g of bis(4-aminophenoxy)dimethylsilane, 7 g of 50% aqueous solution of diethanolamine, and 20 g of acetone in which 1.2 g of N-β-(aminoethyl)-γ-aminopropyltriethoxysilane was dissolved were added under stirring, and the mixture was reacted for 10 min under stirring. 430 g of deionized water was added under rapid stirring for dispersion. Acetone was then separated by distillation to obtain a polyurethane dispersion. The particle size was 133 nm and the solid content was 40 wt %.

[0087] In this example, the aldehyde-free impregnating glue is prepared

[0088] S1: Add WS3 and deionized water into a high-speed disperser in sequence, at 2000 rpm, and disperse for 15 minutes to make a 20% pre-gel for later use.

[0089] S2: Add the aqueous polyurethane dispersion into the dispersion kettle, and stir the shaft at a speed of 300 rpm; add the defoamer and the spreading agent, stir for 10 min, and stir the shaft at a speed of 300 rpm; add the anti-wear agent, stir for 10 min, and stir the shaft at a speed of 500 rpm; finally, add anhydrous ethanol, deionized water, and pre-gel, stir for 15 min, and stir the shaft at a speed of 500 rpm, and adjust the viscosity to 350 mPa·s to prepare the formaldehyde-free impregnating glue.

[0090] Comparative Example 1

[0091] Compared with Example 2, the difference is that polypropylene carbonate polyol, bis(4-aminophenoxy)dimethylsilane chain extender and active monomer N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane are not used.

[0092] The formaldehyde-free impregnating adhesive is prepared from the following raw materials in parts by weight:

[0093]

[0094] Preparation of aqueous polyurethane dispersion IV in this comparative example:

[0095] 250g of dehydrated polybutylene adipate PBA2000, 14g of isophorone diisocyanate, 53g of dicyclohexylmethane diisocyanate, 95g of acetone, and 7.5g of MPEG were added to a 1L four-necked round-bottom flask equipped with a nitrogen inlet and outlet, and the mixture was stirred at 85°C for 3h to react until the NCO% reached 3.92%. After cooling, 210g of acetone was added, and 3.3g of A-95 (N-(2-aminoethyl)-2-aminoethanesulfonic acid), 6.9g of IPDA, and 2g of 50% diethanolamine aqueous solution were added under stirring, and the mixture was reacted for 10min under stirring. 555g of deionized water was added under rapid stirring to disperse the mixture. Acetone was separated by distillation to obtain a polyurethane dispersion. Its particle size was 65nm and the solid content was 35wt%.

[0096] The preparation process of the aldehyde-free impregnated glue in this comparative example is the same as that in Example 2.

[0097] Comparative Example 2

[0098] Compared with Example 1, the difference is that the spreading agent, wear-resistant agent and thickener described in the claims are not used in the preparation process of the impregnating glue.

[0099] The formaldehyde-free impregnating adhesive is prepared from the following raw materials in parts by weight:

[0100]

[0101] The preparation process of the aqueous polyurethane dispersion in this comparative example is the same as that of aqueous polyurethane dispersion I in Example 1.

[0102] The preparation process of the aldehyde-free impregnated glue in this comparative example is the same as that in Example 1.

[0103] Comparative Example 3

[0104] This comparative example is melamine impregnated glue.

[0105] The melamine impregnated adhesive is prepared from the following raw materials in parts by weight:

[0106] Melamine resin dispersion: 98g

[0107] German Woshi 740: 0.5g

[0108] Sodium dioctyl maleate sulfonate: 1.5g

[0109] Preparation of aqueous melamine resin dispersion in this comparative example:

[0110] Accurately weigh each component according to the ratio of the glue base material, add water and formaldehyde solution into the reactor, stir evenly, then add melamine powder, start the stirrer to stir at a speed of (1200 revolutions per minute), raise the temperature to 100°C, and allow the mixed liquid to react for 100 minutes under stirring. When the water-soluble ratio of the liquid is 1:3, add caustic soda into the reactor to adjust the pH value of the mixed liquid to 9.0, cool the glue base mixed liquid to 45°C, add diethylene glycol, stir evenly and set aside;

[0111] Prepared according to the following raw materials in parts by weight:

[0112] 55kg of water, 120kg of 34% formaldehyde aqueous solution by weight, 90kg of melamine powder, and 18kg of diethylene glycol.

[0113] The base paper was impregnated with the impregnated adhesive and dried at 130°C to obtain impregnated adhesive film paper; the impregnated adhesive film paper was hot pressed onto the surface of the artificial board at 8MPa, 150°C, and 1min to obtain the decorative paper veneer artificial board. The impregnated adhesive prepared in the above embodiment was tested according to the national standards GB / T 28995-2012, GB / T 17657-2013, and GB / T 15102-2017, and the test results are shown in Table 1.

[0114] Table 1 Performance test results of various embodiments and comparative examples

[0115] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Glue amount % 120 116 112 100 108 115 Formaldehyde emission mg / L 0 0 0 0 0 1.4 Table bonding strength MPa 0.9 0.8 0.8 0.7 0.6 0.7 Cracking resistance 5 5 5 5 5 4 Scratch resistant qualified qualified qualified Failure Failure qualified Wear resistance mg / 100r 55 65 67 77 79 80 Bending fracture angle 180° 180° 180° 180° 180° 90° Storage time / month ≥6 ≥6 ≥6 ≥6 ≥6 <3 Penetration time / second 6 7 7 14 8 8

[0116] : Finally, it should be noted that the above embodiments are only used to describe the preferred implementation methods of the present invention, rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that various modifications and improvements made by modifying or equivalently replacing the technical solution of the present invention should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A formaldehyde-free impregnating adhesive, characterized in that: The impregnating glue comprises the following components in parts by weight: Wherein, the aqueous polyurethane dispersion contains a bis(4-aminophenoxy)dimethylsilane chain extender with the following structure:

2. The formaldehyde-free impregnating adhesive according to claim 1, characterized in that: The impregnating glue comprises the following components in parts by weight:

3. The formaldehyde-free impregnating adhesive according to claim 1, characterized in that: The aqueous polyurethane dispersion is an aqueous aliphatic polyurethane dispersion with a particle size of 50-150nm and a solid content of 35-40%; And / or, the waterborne polyurethane dispersion is prepared by reacting aliphatic diisocyanate, polyol, catalyst, chain extender and active monomer, emulsifying with water and removing solvent.

4. The formaldehyde-free impregnating adhesive according to claim 3, characterized in that: The aliphatic diisocyanate is selected from one or more of pentamethylene diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate and dicyclohexylmethane diisocyanate.

5. The formaldehyde-free impregnating adhesive according to claim 4, characterized in that: The aliphatic diisocyanate is selected from hexamethylene diisocyanate and / or dicyclohexylmethane diisocyanate.

6. The formaldehyde-free impregnating adhesive according to claim 3, characterized in that: The polyol is a mixture of at least one crystalline polyol having a number average molecular weight of 200-5000 and at least one non-crystalline polyol having a number average molecular weight of 200-5000.

7. The formaldehyde-free impregnating adhesive according to claim 6, characterized in that: The polyol is a mixture of a crystalline diol with a number average molecular weight of 1000-3000 and a non-crystalline diol with a number average molecular weight of 2000-3000.

8. The formaldehyde-free impregnating adhesive according to claim 7, characterized in that: The non-crystalline diol is a polypropylene carbonate polyol prepared by copolymerization using carbon dioxide and propylene oxide as raw materials, and the crystalline diol is a polyester diol prepared by reacting 1,4-butanediol and / or 1,6-hexanediol with adipic acid.

9. The formaldehyde-free impregnating adhesive according to claim 3, characterized in that: The active monomer is one or more of N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, and 1,3-bis(aminopropyl)tetramethyldisiloxane.

10. The formaldehyde-free impregnating adhesive according to claim 9, characterized in that: The active monomer is one or more of N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltriethoxysilane and N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane.

11. The formaldehyde-free impregnating adhesive according to claim 1, characterized in that: The defoamer is an organosilicon defoamer; And / or, the thickener is one or more of fumed silica, sodium carboxymethyl cellulose, hydroxypropyl methyl cellulose, carbomer, and lithium magnesium silicate; And / or, the spreading agent is a polyether-modified trisiloxane wetting agent; And / or, the wear-resistant agent is one or more of silicon dioxide suspension, aluminum oxide suspension, and silicone resin emulsion.

12. The formaldehyde-free impregnating adhesive according to claim 11, characterized in that: The defoamer is BYK-024 and / or BYK-028; And / or, the thickener is hydroxypropyl methylcellulose and / or lithium magnesium silicate; And / or, the spreading agent is one or more of Silwet 618, Silwet 408, and RH-288; And / or, the anti-wear agent is 50%-60% by mass of silicone resin emulsion and / or 10% by mass of aluminum oxide suspension.

13. A method for preparing the formaldehyde-free impregnating adhesive according to any one of claims 1 to 12, characterized in that: The method comprises the following steps: S1: Dispersing thickener and water to form pre-gel; S2: adding the aqueous polyurethane dispersion into a dispersion kettle and stirring (I), adding a defoamer and a spreading agent and stirring (II), adding an anti-wear agent and stirring (III), adding a pre-gel and an auxiliary agent and stirring (IV), adjusting the viscosity, and preparing a formaldehyde-free impregnating glue.

14. The method according to claim 13, characterized in that The dispersion process in S1 is 2000-3000 rpm, and the time is 15-25 min; And / or, the proportion of the thickener in the pre-gel in S1 is 15-30wt%.

15. The method according to claim 13, characterized in that S2: the stirring (I) is at a speed of 300-500 rpm; the stirring (II) is at a speed of 300-500 rpm for 10 min; the stirring (III) is at a speed of 300-500 rpm for 10 min; the stirring (IV) is at a speed of 500-800 rpm for 15 min; And / or, the viscosity in S2 is adjusted to 100-800 mPa·s.

Citation Information

Patent Citations

  • Aldehyde-free artificial board adhesive and aldehyde-free artificial board produced by same

    CN109081902A

  • Preparation method of novel aldehyde-free gum dipped film paper

    CN110450239A

  • Impregnated adhesive film paper facing aldehyde-free artificial board and preparation method thereof

    CN111496948A

  • Formaldehyde-free adhesive for paper impregnated thermosetting resin and preparation method of adhesive

    CN111411543A

  • Formaldehyde-free impregnated film adhesive and preparation method thereof

    CN112921707A